Antenatal Predictors of Adverse Perinatal Outcomes in Preterm Fetuses with Intrauterine Growth Restriction- A Prospective Study - Syed Sahar Zahra, Shagufta Jabeen, Mariyam Javeed, Syeda Tayyba Hussain, Muhammad Asim Iqbal Qureshi, Mian Adnan Aslam Javaid (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In developing countries like Pakistan, health care services and facilities are not optimal so it is difficult to determine the appropriate delivery time in intrauterine growth restriction mothers Objective: This study was conducted to assess predictors of antenatal outcomes in preterm fetuses with intrauterine growth restriction. Methodology: A prospective, cross-sectional study was conducted in the Gynecology and Obstetrics Department of Bahawalpur Medical and Dental College from May 2022 to May 2023. A total of 200 pregnant women with a single pregnancy, gestation age of 24-33 weeks at birth, and Doppler umbilical arterial pulsatility index > 2SD for gestation age at admission were selected by consecutive sampling. Doppler was performed for the umbilical artery, ductus venosus, and middle cerebral artery. The last Doppler assessment was done 24 hours before delivery and the last ultrasound was performed a week before delivery for weight estimation. Birth weight, gestation age at birth, and 1-minute and 5-minute Apgar score were noted. The presence of at least one of the morbid conditions in the NICU was considered an adverse perinatal outcome. Mortality was defined as postnatal death or stillbirth Results: Composite poor outcome was associated with fetal weight, gestation age at birth, reversed end-diastolic velocity, and abnormal DVPI. Birth weight, gestation age, ventilator support, and myocardial dysfunction were strong risk factors for poor outcomes (p<0.001).Gestation age at birth (266/7 and 2907 weeks) and estimated fetal weight (700 and 850 g) were predictors of survival and intact survival respectively. A strong association between birth weight and estimated fetal weight was observed for predicting survival and intact survival. A z score of -3.14 was a good predictor of survival (AUC 0.70, 69.5% specificity, and 71.2% sensitivity) and a score of -3.23 was a good predictor of intact survival (AUC 0.70, 45% specificity, and 80.1% sensitivity). Conclusion: Fetal weight and gestation age were the strongest predictors of neonatal outcomes in preterm fetuses with intrauterine growth restriction. Intact survival was best predicted by fetal weight and gestation age or a combination of Doppler parameters and fetal weight z-scores. Keywords: Intrauterine growth restriction, IUGR, Neonates, Placental insufficiency